Mammary epithelium permeability during established lactation: associations with cytokine levels in human milk - Kivlighan, Katie T.; Schneider, Sallie S.; Browne, Eva P.; Pentecost, Brian T.; Anderton, Douglas L.; Arcaro, Kathleen F. (Frontiers in Nutrition, 2024)
Objective: The cytokine profile of human milk may be a key indicator of mammary gland health and has been linked to infant nutrition, growth, and immune system development. The current study examines the extent to which mammary epithelium permeability (MEP) is associated with cytokine profiles during established lactation within a sample of US mothers. Methods: Participants were drawn from a previous study of human milk cytokines. The present analysis includes 162 participants (98 Black, 64 White) with infants ranging from 1-18 months of age. Levels of cytokines were determined previously. Here we measure milk sodium (Na) and potassium (K) levels with ion-selective probes. Two approaches were used to define elevated MEP: Na levels ≥ 10 mmol/L and Na/K ratios greater than 0.6. Associations between maternal-infant characteristics, elevated MEP, and twelve analytes (IL-6, IL-8, TNFα, IL-1β, FASL, VEGFD, FLT1, 27 bFGF, PLGF, EGF, leptin, adiponectin) were examined using bivariate associations, principal components analysis, and multivariable logistic regression models. Results: Elevated MEP was observed in 12% and 15% of milk samples as defined by Na and Na/K cutoffs, respectively. The odds of experiencing elevated MEP (defined by Na ≥ 10 mmol/L) were higher among Black participants and declined with older infant age. All cytokines, except leptin, were positively correlated with either Na or the Na/K ratio. A pro-inflammatory factor (IL-6, IL-8, TNFα, IL-1β, EGF) and a tissue remodeling factor (FASL, VEGFD, FLT1, bFGF, PLGF, adiponectin) each contributed uniquely to raising the odds of elevated MEP as defined by either Na or the Na/K ratio. Conclusion: This exploratory analysis of MEP and cytokine levels during established lactation indicates that elevated MEP may be more common in US populations than previously appreciated and that individuals identifying as Black may have increased odds of experiencing elevated MEP based on current definitions. Research aimed at understanding the role of MEP in mammary gland health or infant growth and development should be prioritized.